2007
DOI: 10.1111/j.1439-0442.2007.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Xylazine Premedication does not Modify the Onset and Duration of Cisatracurium Blockade in Anaesthetized Dogs

Abstract: The purpose of this study was to evaluate the effect of xylazine as premedication on the onset time and duration of cisatracurium neuromuscular blockade in anaesthetized dogs. This study was carried out on 12 healthy dogs aged 0.5-6 years and weighing 9-26 kg undergoing various elective surgical procedures. The dogs were randomly divided into two groups of t (test) and c (control), with six dogs each. In group t, premedication was conducted using acepromazine maleate 0.3 mg kg(-1) and xylazine 0.3 mg kg(-1) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The possible cis-atracurium potentiation by fentanyl and lidocaine did not influence the duration of the NMB, which was shorter in dogs administered fentanyl. Accordingly, the duration of the NMB was similar to that described in other studies for isoflurane-anaesthetised (27 (24–31) minutes)4 and halothane-anaesthetised dogs (28.3±10.2 minutes and 28.3±5.46 minutes) 1 20. In addition, the body temperature of dogs administered fentanyl was, among groups, the most adequate for the species.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The possible cis-atracurium potentiation by fentanyl and lidocaine did not influence the duration of the NMB, which was shorter in dogs administered fentanyl. Accordingly, the duration of the NMB was similar to that described in other studies for isoflurane-anaesthetised (27 (24–31) minutes)4 and halothane-anaesthetised dogs (28.3±10.2 minutes and 28.3±5.46 minutes) 1 20. In addition, the body temperature of dogs administered fentanyl was, among groups, the most adequate for the species.…”
Section: Discussionsupporting
confidence: 82%
“…In previous studies, the NMB onset after cis-atracurium was longer in dogs administered acepromazine (2.5±0.6 minutes and 6.2±1.4 minutes),1 20 dexmedetomidine (3.8 (2.6–5) minutes)4 and acepromazine plus xylazine (3.2±1.4 minutes)20 compared with the present study. Alpha-2 adrenoceptor drugs produce central muscle relaxation through inhibition of noradrenaline release in interneurons of the spinal cord, which can potentiate the NMB effects of a nondepolarising muscle relaxant 15 20. However, the significant, despite poor, positive correlation between the dose of medetomidine and the onset time of the NMB was not considered to be the primary cause of the reduction of the NMB onset.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…5 Data from the latter study indicated that the onset time of the NMB induced by cis-atracurium can be shortened in isoflurane-anaesthetised dogs administered fentanyl and lidocaine. 5 It can also be influenced by others drugs that affect muscle contractility and/or cardiac output, such as benzodiazepines, 6 acepromazine, 7 alpha-2 adrenoceptor agonist drugs, 7,8 propofol 9,10 and inhalant agents. 10,11 To date, there has been no study in cats comparing cisatracurium and different anaesthetic protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia was induced with propofol (Proposure 10 mg mL −1 ; Boehringer Ingelheim Animal Health Italia SpA, Noventana (PD), Italy) at the dosage of 4–6 mg kg −1 intra-venously (IV) to effect. In Group B, the administration of propofol was immediately followed by a single IV bolus injection of cisatracurium 0.2 mg kg −1 (Nimbex 2 mg mL −1 Glaxo, SmithKline SpA, Verona, Italy) [ 3 , 7 , 14 ].…”
Section: Methodsmentioning
confidence: 99%